Pharmacist educational interventions program for outpatients with chronic heart failure. Issue 2 (12th March 2012) - Florit, M.; Barrantes, M.; Luque, S.; Berenguer, N.; Comín-Colet, J.; Carmona, A.; Salas, E.
Abstract : Background: Patients with chronic heart failure (CHF) take several medicines and frequently manage their medicines inappropriately. In our hospital, a postdischarge pharmacist educational interventions program (PEIP) has been introduced as a part of a multidisciplinary CHF disease management program. Purpose: To describe CHF patient profiles, adherence, treatment knowledge and detection of drug-related problems (DRP) through the PEIP. To analyse the relation between DRPs detected and CHF patient characteristics. Materials and methods: Prospective observational study including all CHF patients attending the PEIP from May 2010 to August 2011. Data: demographics; New York Heart Association (NYHA) class; mean ejection fraction (EF); cardiovascular risk factors (CRF); self-administration of medicine (SA); self-reported adherence to diet (AD) and medicine (AM) and motivation (M) (Modified Morisky Scale); knowledge of CHF medicines: %dose (D), frequency (F) and indication (I); contraindicated drugs (CID) and DRP (DRP1: did not use a needed medicine; DRP2: used a medicine not needed; DRP3: ineffective treatment; DRP4: infradose; DRP5: overdose; DRP6: adverse reaction) and cases of acute decompensation. Statistical test: χ 2 and Fischer exact test for dichotomous variables and t-test for continuous variables. Results: Patients: 75. Patient profile: 54 (72%) male; age: 71.8±1.3; patients/NYHA class: I: 2 (2.7%); II: 58 (77.3%); III: 14 (18.7%); IV: 1 (1.3%), EF< 45%: 42(56%); smokers: 20(26.7%); alcohol consumption: 17(22.7%). Adherence and knowledge: SA: 41(54.7%); AD: 56(74.7%); AM: 75(100%); M: 61(81.3%); Mean knowledge of CHF medicine: DFI: 29.7%± 32.0; DF: 47.8%± 41.5; patients who were aware of CID: 12(16%). DRP: 17 patients (22.7%); DRP1: 9 (12%); DRP2: 2(2.7%); DRP3: 6 (8%); DRP4: 3 (4%); DRP5: 2 (2.7%); DRP6: 4(5.3%). Patients with decompensation: 11(14.7%). Comparison between patients with and without DRP: decompensated: 5/17(29.4%) versus 6/58(10.3%)(p=0.05); SA: 12/17(70.6%) versus 29/58(50%)(p=0.134). No other significant differences were observed between the two groups. Conclusions: The PEIP evaluated the adherence and knowledge of the treatment in CHF patients and allowed us to detect DRPs in about 23% of the patients. The presence of any DRP was only correlated with acute decompensation and self-administration of drugs, suggesting the importance of an appropriate CHF treatment self-management.